Analisis Komparatif Performa Algoritma AES Dan RSA Dalam Keamanan Data Digital Berbasis Python - Habib Nurfaizal; Abdul Choliq; Fahrul Roji; Ayu Permatasari (BETRIK, 2026)
Data security is a crucial aspect of digital information exchange. System developers are often faced with the choice between the symmetric algorithm Advanced Encryption Standard (AES), which is fast but has challenges in key distribution, and the asymmetric algorithm Rivest–Shamir–Adleman (RSA), which provides more secure key distribution but incurs higher computational overhead. In addition, studies examining the performance efficiency of these two algorithms across various file sizes and types remain limited. This study aims to analyze the performance comparison between AES and RSA based on encryption and decryption time as well as computational efficiency. The method used is an experimental approach through simulation using the Python programming language with a graphical user interface (GUI). Testing was conducted on various file types and sizes, namely .txt (1 KB, 2 KB), .doc (48 KB), .pdf (97 KB), .png (122 KB), and .jpg (359 KB). The experimental results show that AES tends to be more efficient and faster for medium to large-sized files, while RSA demonstrates more stable performance on small file sizes but is less efficient for larger files due to its computational complexity. Therefore, AES is more recommended for primary data encryption, while RSA is effectively used for secure key distribution mechanisms.